Group memory rehabilitation for people with multiple sclerosis: a feasibility randomized controlled trial - Carr, Sara; das Nair, Roshan; Schwartz, Annette; Lincoln, Nadina (SAGE, 2014)
Objective: To assess the feasibility and effectiveness of a group memory rehabilitation programme combining compensation and restitution strategies. Design: Randomized controlled trial.